The Effect of Using a Knee Decker to Reduce Knee Pain in Farmers - Suprayogi, Dody; Fathi, Muhammad; Kotimah, Nurul (Poltekkes Kemenkes Jakarta I, 2023)
Background: Farmers are people who carry out activities in the agricultural sector, both garden farming, fields, rice fields, fisheries, and others on land with the aim of obtaining economic benefits. Farmers have prevalence of knee pain symptoms that lead to reduced mobility and ability to work. Knee pain occurs due to heavy and continuous pressure such as standing, squatting, lifting crops, and hoeing. In this case to treat knee pain using a tool in the form of a knee lifter to determine the ability to reduce knee pain. Objective: To determine the effect of using a knee decker on reducing the degree of knee pain in farmers in Mojopuro Village, Sragen Regency. Methods and Subjects: This research was conducted from March to April in Mojopuro Village, Sragen Regency using a quantitative research method using a quasi-experimental one group pre-test and post-test design. The sampling technique used is purposive sampling. The subjects used were all farmers who experienced knee pain. Results: A statistical analysis with a p-value 0.000 less than 0.05 revealed that using a knee decker had a substantial impact on lowering the severity of knee pain in farmers by 43% from a sample of 25 people who had knee pain Conclusion: There is an effect of using a knee decker to reduce the degree of knee pain in farmers, so that increasing mobility and ability to work.